Evaluating the effectiveness of pharmacological intervention vs placebo in speech-language therapy for children with delayed language due to recurrent otitis media - Rasha Sami; Hebatallah S. Hashem; Sherine Ramzy (The Egyptian Journal of Otolaryngology)
Abstract Purpose This study assesses the impact of speech-language therapy (SLT) combined with Speak Smooth medication compared to SLT with vitamin B12 supplements as a placebo in children aged 5 to 8 years who exhibit delayed language resulting from recurrent otitis media (OM). Following 6 months of therapy, an evaluation was conducted to ascertain whether the Speak Smooth medication provided more benefits to children compared to those getting speech and language therapy and a placebo. Method Thirty children diagnosed with delayed language resulting from recurrent otitis media (OM) were allocated into 2 groups, each including 15 children. Group 1 was administered the Speak Smooth medication, whereas Group 2 was given vitamin B12. Both groups underwent speech and language therapy for 6 months, after which their language outcomes were compared to determine if Speak Smooth may enhance the overall language score of children with delayed language. Results No statistically significant differences were seen between the two groups, indicating that Speak Smooth did not enhance language development beyond the effects of structured speech and language therapy. Conclusion Children receiving speech and language therapy (SLT) with Speak Smooth medication show no significant enhancement in receptive and expressive language scores relative to those getting SLT with vitamin B12. These data suggest that SLT is crucial for addressing delayed language, and that the incorporation of Speak Smooth or vitamin B12 will not yield supplementary advantages. Future study should investigate evidence-based strategies that enhance the effectiveness of speech-language therapy, encompassing early intervention, caregiver participation, and customized therapeutic approaches.